Perceived Dangerousness Mediates Punitive Attitudes Toward Sex Offenders: Results From a Vignette Experiment - Kruis, Nathan E. (Crime & delinquency, 2025)
The current study used an experimental vignette (n = 1,093) to examine the effects of perpetrator sex and age, and victim sex and age, on simulated juror sentencing recommendations for individuals convicted of sexual offenses (ICSO). Path analyses were used to see if differences in punitive attitudes could be explained by perceptions of dangerousness participants attached to experimentally manipulated variables, as hypothesized by attribution theorists. Results show that participants consistently recommended longer sentences, higher fines, and indicated greater support for post-release sanctions for male offenders, older perpetrators, and for offenders who victimized younger adolescents. Path analysis demonstrated that perceptions of dangerousness partially mediated the relationship between experimentally manipulated predictor variables and recommended sentence length, providing partial support for attribution theory.